Interrater reliability in the temporal quantitative analysis of oropharyngeal swallowing using a specific software - Cola, Paula Cristina; Alves, Thaís Coelho [UNESP]; Gatto, Ana Rita [UNESP]; Rubira, Claudio José; Spadotto, André Augusto [UNESP]; da Silva, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2022)
Purpose: This study aims to analyze inter-judge reliability by measuring a few temporal parameters of swallowing using a specific software. Methods: Six databases that include the results of reliability tests performed in prior studies by the present research group were employed. The datasets were obtained using the same measurement method and include data obtained based on puree (level 3) consistency and liquid (level 0) consistency according to the International Dysphagia Diet Standardization Initiative. In this study, the reliabilities corresponding to the total oral transit time (TOTT), initiation of the pharyngeal response time (PRT), and the pharyngeal transit time (PTT) were measured using the same software; the evaluations performed by a single rater for all datasets were used as the benchmark, and evaluations performed by new raters for each dataset were also included. The intra-class correlation coefficient (ICC) with a 95% confidence interval was employed. Results: A total of 244 videofluoroscopic swallowing study images were analyzed. In all analyses, the ICCs were >0,75 and showed excellent agreement between the senior and junior raters. The TOTT for level 3 showed ICCs from 0.936 to 1.000 and that for level 0 showed ICCs from 0.997 to 1.000. Further, the PRT showed ICCs from 0.916 to 1.000 for level 3 and from 0.978 to 1.000 for level 0. The PTT showed ICCs from 0.848 to 1.000 for level 3 and from 0.984 to 1.000 for level 0. Conclusion: The reliabilities obtained using this specific software for the TOTT, PRT, and PTT showed excellent agreement.
Confiabilidade entre avaliadores na análise quantitativa temporal da deglutição orofaríngea por meio de software específico
Keywords: Concordância; Deglutition Disorders; Deglutição; Reliability; Software; Swallowing; Tempo; Time; Transtornos de Deglutição